2015
DOI: 10.1039/c5ra10714h
|View full text |Cite
|
Sign up to set email alerts
|

Novel architecture for anomalous strengthening of a particulate filled polymer matrix composite

Abstract: We propose an architecture for dramatically enhancing the stress bearing and energy absorption capacities of a polymer based composite. Different weight fractions of iron oxide nano-particles (NPs) are mixed in a poly(dimethylesiloxane) (PDMS) matrix either uniformly or into several vertically aligned cylindrical pillars.These composites are compressed up to a strain of 60% at a strain rate of 0.01 s À1 following which they are fully unloaded at the same rate. Load bearing and energy absorption capacities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The main mechanism of heat dissipation in polymers is attained by phonon transfer , Li and McGaughey, 2015, Idumah and Hassan 2016b, Regner et al 2016. Phonons transport heat energy by interacting with each other and with subatomic particles (Reddy et al 2015, Regner et al 2016. Imperfections in the polymer lattice such as dislocations, impurities, and voids have capabilities of introducing irregularities resulting in phonon scattering (Santos et al 2013, Kamseu et al 2015.…”
Section: Polymer Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The main mechanism of heat dissipation in polymers is attained by phonon transfer , Li and McGaughey, 2015, Idumah and Hassan 2016b, Regner et al 2016. Phonons transport heat energy by interacting with each other and with subatomic particles (Reddy et al 2015, Regner et al 2016. Imperfections in the polymer lattice such as dislocations, impurities, and voids have capabilities of introducing irregularities resulting in phonon scattering (Santos et al 2013, Kamseu et al 2015.…”
Section: Polymer Thermal Conductivitymentioning
confidence: 99%
“…Thus, in order to ensure efficient operational performance of these devices, the unwanted heat generated needs to be rapidly dissipated. The possession of high thermal conductivity is essential for effective dissipation of heat to enable the optimum performance temperature of devices to be kept at very low levels so as to eliminate dielectric degradation caused by overheating (Ngo and Byon 2015, Reddy et al 2015, Regner et al 2016. Hence, the enhancement of heat dissipation abilities of materials used in these sensitive devices has become very crucial (Lee et al 2012a,b).…”
Section: Introductionmentioning
confidence: 98%
“…Z 0 is the internal impedance of the material with A 1 , A 3 and c 1 as positive constants and A 2 a negative constant. In a previous study, Reddy et al showed that there is non-linear dependence of stress-strain in PDMS foam-like structures [57]. It can be concluded that the non-linear response is due to the PDMS structure of the device but not the characteristics of the device.…”
mentioning
confidence: 98%